Fetal Growth and Childhood Acute Lymphoblastic Leukemia: Findings from the Childhood Leukemia International Consortium (CLIC) - Milne, Elizabeth (2013)
Positive associations have been reported between measures of accelerated fetal growth and risk of childhood acute lymphoblastic leukemia (ALL). We investigated this association by pooling individual-level data from 12 case-control studies participating in the Childhood Leukemia International Consortium. Two measures of fetal growth – weight-for-gestational-age and proportion of optimal birth weight (POBW) – were analysed. Study-specific odds ratios (ORs) and 95% confidence intervals (CIs) were estimated using multivariable logistic regression, and combined in fixed effects meta-analyses. Pooled analyses of all data were also undertaken using multivariable logistic regression. Subgroup analyses were undertaken when possible. Data on weight for gestational age were available for 7,348 cases and 12,489 controls from all 12 studies and POBW data were available for 1,680 cases and 3,139 controls from three studies. The summary ORs from the meta-analyses were 1.24 (95% CI 1.13, 1.36) for children who were large for gestational age relative to appropriate for gestational age, and 1.16 (95% CI: 1.09, 1.24) for a one standard deviation increase in POBW. The pooled analyses produced similar results. The summary and pooled ORs for small-for-gestational-age children were 0.83 (95% CI: 0.75, 0.92) and 0.86 (95% CI 0.77, 0.95) respectively. Results were consistent across subgroups defined by sex, ethnicity and immunophenotype, and when the analysis was restricted to children who did not have high birth weight. The evidence that accelerated fetal growth is associated with a modest increased risk of childhood ALL is strong and consistent with known biological mechanisms involving insulin like growth factors.